THE USE OF PICTURE TO IMPROVE STUDENTS’ ABILITY IN WRITING SKILL OF EIGHTH GRADE STUDENTS IN SMP NEGERI 1 MAKARTI JAYA BANYUASIN SUMATERA SELATAN - Hartini Agustiawati; Ressy Novasyari; Ambar Wati; Melisa Novianty; Nike angraini (Journal of Research in Social Science and Humanities, 2024)
The topic of this study is “The use of pictures to improve the writing skills of eight grade students of SMPN 1 Makarti Jaya Banyuasin”. This discussion of this lesson is to answer the question of is there a significant improvement between students learning to use pictures learning to use pictures and not to use picture?In this study, researcher used quansi experiments using pre test and post test. The population is eighth grade,especially grade 8.1 and 8.5. One of the classes used as the experimental class is class of 8.5 and the control class is class of 8.1.     The use of media image to improve students writing skills is applied to the experimental class, namely class of  8.5. While the control class does not use images. Each class held treatment and the research lasted for 16 meetings with different pictures at each meeting.From the results of the pretest and post test that have been carried out, the researcher gets the maximum result, namely the valueon the pretest 72% to 78% in the post test. Before holding the post test with the same picture,students were given treatment for 14 meetings. From the results of this study, this means that the use of images can improve students writing skills. The data collection was carried out using the SPSS application.